2011
DOI: 10.1088/0957-4484/22/31/315606
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon-encapsulated iron nanoparticles by pyrolysis of iron citrate and poly(vinyl alcohol): a critical evaluation of yield and selectivity

Abstract: Carbon-encapsulated iron nanoparticles were synthesized by pyrolysis at 1000 °C of two solid precursors: poly(vinyl alcohol) and iron citrate. The weight ratio between the precursors controlled the reaction yield, crystallinity, morphological features and magnetic properties of the products. The encapsulation yield of iron nanoparticles in carbon shells was strongly influenced by the iron-to-carbon ratio and depended on the iron citrate content in the initial reactant mixtures. Despite the inherent simplicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…This is the same trend as reported previously [23]. The reason was that more copper enabled a higher amount of lignin to be oxidized into carbonaceous gases vaporizing during the redox process of reducing copper ions to atoms and rendering the loss of carbon material.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This is the same trend as reported previously [23]. The reason was that more copper enabled a higher amount of lignin to be oxidized into carbonaceous gases vaporizing during the redox process of reducing copper ions to atoms and rendering the loss of carbon material.…”
Section: Resultssupporting
confidence: 88%
“…The particle size decreased significantly when the weight ratio increased from 1:2 to 1:1, while the particle diameter increased significantly when the weight ratio increased from 1:4 to 1:2. The particle size’s downward trend was similar to the observation from the study of mixing poly (vinyl alcohol) with iron citrate, with an iron-to-carbon weight ratio increasing up to 7:9 [23], and from another study wherein ferrocene and aromatic heavy oil was mixed with a ferrocene-to-oil weight ratio increasing up to 7:20 [26]. However, the extent of size decline was lower than the one with copper because iron has a carbon solubility much higher than copper, which can prevent carbon from effectively acting as a barrier to prevent the agglomeration of iron nanoparticles [27].…”
Section: Resultssupporting
confidence: 75%
“…In general, as the temperature increased from 700 to 900 • C, the diffraction intensity of α-Fe decreased while the γ-Fe increased, and as the temperature further increased to 1000 • C, the γ-Fe diffraction intensity (2θ = 43.6 • ) decreased, while the Fe 3 C intensity appeared. The existence of γ-Fe starting at 700 • C indicated that the γ-Fe was somehow shielded or blocked in the carbon matrix, preventing the phase transformation of γ-Fe to α-Fe and Fe 3 C [25,26] at ambient conditions, because at ambient conditions γ-Fe is thermodynamically unstable and normally transforms to α-Fe and Fe 3 C spontaneously [17]. The iron phase shifting from α-Fe to γ-Fe started at 700 • C, which is lower than the bulk iron phase transformation (α-Fe to γ-Fe) temperature of 727 • C [27].…”
Section: Xrdmentioning
confidence: 99%
“…During this process, polymers first decompose to amorphous carbon (AC), after which AC, as the solid carbon source, dissolves in and precipitates out of the catalyst [16][17][18][19][20][21]. The dissolution and precipitation of AC is affected by the thermal treatment temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that for each fabrication method of magnetic carbon nanoparticles there are more or less some metallic nanoparticles which are nonencapsulated or encapsulated in defective carbon coatings. We did acid treatment to our product (4 M HCl for 24 h) [23], VSM pattern of the acid-treated product was shown in Fig. 3(c), where the contribution of paramagnetism signals of the sample was deducted.…”
Section: Resultsmentioning
confidence: 99%